2017
DOI: 10.1007/978-3-319-61204-1_5
|View full text |Cite
|
Sign up to set email alerts
|

No Free Charge Theorem: A Covert Channel via USB Charging Cable on Mobile Devices

Abstract: More and more people are regularly using mobile and batterypowered handsets, such as smartphones and tablets. At the same time, thanks to the technological innovation and to the high user demands, those devices are integrating extensive functionalities and developers are writing battery-draining apps, which results in a surge of energy consumption of these devices. This scenario leads many people to often look for opportunities to charge their devices at public charging stations: the presence of such stations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…For a targeted attack, an attacker may physically access the phone to fetch the malicious battery with the recorded power trace. Alternatively, the battery may manipulate the reported charge level to force the phone's owner to connect to a malicious charger, which in turn may relay the data to an outside attacker [30]. To trigger this behavior in a specific location equipped with malicious chargers, the battery may identify the browsing event to a gateway for connecting to a public hotspot.…”
Section: Fig 2 Microcontroller Inside the Battery Of Samsung Galaxy S4mentioning
confidence: 99%
“…For a targeted attack, an attacker may physically access the phone to fetch the malicious battery with the recorded power trace. Alternatively, the battery may manipulate the reported charge level to force the phone's owner to connect to a malicious charger, which in turn may relay the data to an outside attacker [30]. To trigger this behavior in a specific location equipped with malicious chargers, the battery may identify the browsing event to a gateway for connecting to a public hotspot.…”
Section: Fig 2 Microcontroller Inside the Battery Of Samsung Galaxy S4mentioning
confidence: 99%
“…It achieves this by cutting off the data pins in the USB cable and allowing only the power pins to connect through. However, this solution does not work for certain charging attacks like PowerSnitch [37], which can leak information via analyzing power consumption.…”
Section: User Feedbackmentioning
confidence: 99%
“…where they presented Mactans, a malicious charger to launch charging attacks by injecting malware on an iOS6 device based on BeagleBoard during the charging process. Spolaor et al [37] then proposed PowerSnitch, a malicious application that can utilize power consumption to send out data over a USB charging cable to the public charging station. Since we are not sure that these charging facilities are not maliciously controlled by cyber-criminals including charging station developers, maintenance managers and Government agencies, there is a need to pay particular attention on charging vulnerabilities in public charging facilitates.…”
Section: Introductionmentioning
confidence: 99%
“…The authors manipulated the charger to measure the current input to the phone and could reconstruct the leaked data stream by analysing the recorded power trace. In contrast to Spolaor et al [19], in this work we will not use any external devices to establish the covert channel but only rely on internal device measurements. Further, we will directly transfer data from one application to another within the device, which can leak the data later via conventional communication interfaces.…”
Section: Related Workmentioning
confidence: 99%
“…Using this map, the authors were able to reconstruct the movement trajectory of a mobile device by analysing the power trace. Spolaor et al [19] showed that it is possible to extract data from a charging phone by modulating the amount of power which is taken in via the charger, by changing the utilization of the mobile phones processor. The authors manipulated the charger to measure the current input to the phone and could reconstruct the leaked data stream by analysing the recorded power trace.…”
Section: Related Workmentioning
confidence: 99%